Exploring Social and Individual Influences on Teenagers’ Mental Well-Being (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Mental health encompasses more than the absence of illness; it represents a fundamental dimension of overall quality of life. Adolescence, marked by rapid emotional and social changes, often exposes individuals to various stressors. Teenagers should possess the ability to effectively cope with these situations. Many teenagers, however, struggle to cope with adverse experiences, leading to compromised psychological well-being. There is a need to identify the factors which adversely impacts on their mental wellness. This study aimed to identify key factors influencing the mental health of teenagers and to assess their overall mental well-being. Employing a quantitative, descriptive research design, data were collected from a randomly selected sample of 40 adolescents using a structured questionnaire. The major findings are –there are many social and individual factors affecting mental health such as gender, organizational environment, social background, Parental occupation, locality, Parental education. The study underscores the need for targeted interventions and strategies to foster resilience and promote sound mental well-being among teenagers.